An Analysis of Students’ Difficulties in Understanding English Reading Texts at Class VIII MTs Qamarul Huda Level - Nurainun Putri; Hasbullah Hasbullah; Herman Herman (Universitas Qamarul Huda Badaruddin, 2026)
This study investigates the difficulties faced by eighth-grade students at MTs Qamarul Huda in understanding English reading texts and the factors contributing to these challenges. Data were gathered through reading tests, classroom observation, interviews, and documentation. The findings revealed that students primarily struggled with limited vocabulary, identifying main ideas, making inferences, and understanding details. The root causes were both linguistic such as insufficient vocabulary and complex sentence structures and non-linguistic, including lack of motivation, poor reading habits, and monotonous teaching strategies. The study suggests implementing interactive teaching methods and vocabulary enrichment to improve reading comprehension. These findings provide valuable insights for teachers, students, and researchers to enhance English reading instruction